PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH a QUESTION TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 14 PADANG - Fadila, Titin; Rahmi, Rahmi; Haryono, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
The background of this research is about lower of studentsâ mathematics concept comprehension at eighth grade students of SMPN 14 Padang. The purposes of this research is to see the effect of using active learning tipe Learning Starts With a Question strategy was better than studentsâ concept comprehension which using konvensional learning toward studentsâ at eighth grade SMPN 14 Padang and to see the effectiveness of using active learning type Learning Starts With a Question strategy in mathematics study at eight grade studentsâ SMPN 14 Padang. The researcher got validity of the data from table distribution to experimental class. The researcher mannered the result of the data by using Mann-Whitney test then used the result post test which using indicator of concept comprehension MINITAB also help the researcher to analyse the data, the researcher got probabilitas=0.0285, is smaller than 0,05. In conclusion, the studentsâ mathematics concept comprehension by using active learning type Learning Starts With a Question strategy is better than using konvensional learning in studentsâ mathematics concept.